GULLY’S MONITORING: MORFOMETRIC AND SEDIMENTS STUDY AT BRAZIL’S SAVANNA - Roberto Reis Alves; Ricardo Reis Alves; Silvio Carlos Rodrigues (Sociedade & Natureza)
The intense processes of the society development and the economy in the industrialist and agricultural scope had taken to an antropogenic raised in the environment having provoked a degradation sped up in exactly, factor this lot of due to form of disordered occupation in all the country and it was not different in the region of the Triângulo Mineiro in special in the region of the city of Uberlândia, which also felt the consequences of this occupation without planning. The place chosen for study is situated in a micro-basin, tributaryof the Mogi Stream that is direct affluent of the Lagoinha Stream, which is tributary of the Uberabinha River, which is the main reserve of water of the city of Uberlândia MG. The erosive processes that occur inside the Lagoinha Basin were very interesting, in special those of bigger intensity, which is called gullies. The gully in question is situated at cartographic coordinates (UTM) 0788237 and 7903448 and the altitude is approximately 857m and was chosen by if dealing with an evolution unchained for Human kind action (Burnt, Tread of the cattle, etc) and sped up by the intemperic action (rains mainly). The area presents relief with little inclined form (hills), which are intercalated by shallow valleys. Moreover, the ground are sandy, acid and little cohesive, with presence of peat bogs, and exist in the high source one strong hydromorfic influence. It is necessary to mention that, to the long of the stream, a waterfall was formed that catalyzed the force of consuming of the water and facilitating the begin of the erosive process, that resulted in gully. When the relief is analyzed, cannot be forgotten the question of index declivity of one determined area, therefore this index contributes to determines the conditions of the superficial draining, influencing directly in the draining speed. In the area of the basin the declivities vary since low indices 2%, what contributes to determine a draining with speed low, until relatively high indices for the region between 12 and 16%. In the places where the declivity index is higher, associated to the Human kind occupation which causes a waterproofing of the ground, are where if perceives a bigger energy in the superficial draining, that in some intent rain hours can be responsible forremodelling significant in the forms of the urban landscapes. Therefore, the intention of the study is to understand the main transformations that the relief comes suffering, from the intensification of the flow of antropics actions in the Cerrado (Savanna) and inside of all this context the intention is to guide quickly the degradation reorganization that the environment suffered and still it suffers, being searched indicating to understand the current problems there, in special those on to the degradation in the environment of the Cerrado, offering resources that can serve the recovery least or the of this environment.